Pengembangan Materi Layanan Informasi Studi Lanjut Berbantuan Media Sosial Instagram untuk Perencanaan Karier Siswa SMA - Muslihati Muslihati; Muslihati Muslihati; Via Puspita Lindasari; Henny Indreswari; Via Puspita Lindasari (Universitas Negeri Malang, 2021)
Abstract: This research aims to produce further study information service materials assisted by Instagram social media for high school student career planning in an effort to facilitate information on secondary school students of SMAN 1 Durenan, Trenggalek. The research used is research and development using the Reach and Development model. The research steps carried out began with knowing the problem, carrying out need assessment, formulating objectives, designing the initial product, expert testing (material experts & media experts) and user testing (counselors), revisions of the results of expert testing and user testing, after design and material revisions ready to use. Data collection was carried out twice, namely pre-development data collection and post-development data collection. Pre-development data collection was carried out by interviewing counselors and students via WhatsApp, as well as distributing statement forms to students. The results show that students at SMA Negeri 1 Durenan have not been able to plan their secondary school well so that further study information services need to be provided in order to find suitable alternative secondary schools. Therefore, researchers developed further study information service materials assisted by Instagram social media. Furthermore, post-development data collection is by conducting validity tests on media experts, material experts and testing prospective users (counselors). The results showed that the advanced study service material products developed were very acceptable and could be used by students in exploring secondary schools. Abstrak: Penelitian ini bertujuan menghasilkan materi layanan informasi studi lanjut berbantuan media sosial instagram untuk perencanaan karier siswa SMA dalam upaya memfasilitasi informasi sekolah lanjutan siswa SMAN 1 Durenan, Trenggalek. Penelitian yang digunakan yaitu penelitian dan pengembangan dengan menggunakan model Reach and Development. Langkah penelitian yang dilakukan diawali dengan mengetahui masalah, melakukan need assessment, merumuskan tujuan, mendesain produk awal, uji ahli (ahli materi & ahli media) dan uji pengguna (konselor), revisi dari hasil uji ahli dan uji pengguna, setelah revisi desain dan materi siap digunakan. Pengumpulan data dilakukan sebanyak dua kali yakni pengumpulan data pra pengembangan dan pengumpulan data pasca pengembangan. Pengumpulan data pra pengembangan dilakukan dengan wawancara kepada konselor dan siswa, serta penyebaran form pernyataan kepada siswa. Hasil menunjukkan bahwa siswa di SMA Negeri 1 Durenan belum mampu merencanakan sekolah lanjutan mereka dengan baik sehingga perlu diberikan layanan informasi studi lanjut agar dapat menemukan alternatif sekolah lanjutan yang sesuai. Oleh karena itu peneliti mengembangkan materi layanan informasi studi lanjut berbantuan media sosial instagram. Selanjutnya pengumpulan data pasca pengembangan yaitu dengan cara melakukan uji validitas kepada ahli media, ahli materi dan uji calon pengguna (konselor). Hasil menunjukkan bahwa produk materi layanan studi lanjut yang dikembangan sangat berterima dan dapat digunakan oleh siswa dalam mengeksplorasi sekolah lanjutan.